In this chapter we are going to learn the concept of exponential terms with base negative which means
the base number is negative, for instance (3)^{4}.
Let us try to solve the example, for a while assume 3 as 3 and now 3 is multiplied itself for 4 times,
i.e., 3 x 3 x 3 x 3 we get 81. We got 81 for 3^{4}, now depend on the exponent (even or odd) we get the final result.
Exponent 4 is even, thus (3)^{4} is 81.
Therefore we get the result for (3)^{4} as 81.
Let us try to solve one more example taking the exponent odd, i.e., (2)^{7}
For sometime assume 2 as 2, now 2 is multiplied itself for 7 times, i.e., 2 x 2 x 2 x 2 x 2 x 2 x 2,
we get as 128 for 2^{7}.
Depend on the exponent (even or odd) we get the final result for (2)^{7} here we have 7 which is odd.
Thus we get the result as negative for (2)^{7} .
Therefore we get the result for (2)^{7} as 128.
Few more examples :
 (1)^{4} = 1 x 1 x 1 x 1 = 1
 (1)^{3} = 1 x 1 x 1 = 1
 (1)^{3} = (1) x (1) x ( 1) = 1
 (1)^{4} = (1) x (1) x (1) x (1) = 1
 (1)^{5} = (1) x (1) x (1) x (1) x (1) = 1
The below concept is to be remembered :
 If (a)^{m}= a^{m} , m is odd
 If (a)^{m} = a^{m} , m is even

(3)^{4}
 (a)^{4}
 (5)^{3}
Let us try to solve few more examples :
In the first example (3)^{4} = (3) x (3) x (3) x (3) = 81
Therefore the result for (3)^{4} = 81.
Coming to second example (a)^{4} = (a) x (a) x (a) x (a) = a^{4}.
Therefore the result for (a)^{4} = a^{4}.
Therefore the result for (5)^{3} = 1/125.
In the last example (5)^{3} = 1/(5)^{3} = (1)/125. ( since a^{m} = 1/a^{m})
The examples have been illustrated in the video below :